A methodology for the prediction of suceptibility of stress corrosion creacking - Galvele, José Rodolfo (Comisión Nacional de Energía Atómica; Argentina, 1977)
Fil: Galvele, José Rodolfo Comisión Nacional de Energía Atómica; Argentina